2013
DOI: 10.1144/sp394.8
|View full text |Cite
|
Sign up to set email alerts
|

Using titanium-in-quartz geothermometry and geospeedometry to recover temperatures in the aureole of the Ballachulish Igneous Complex, NW Scotland

Abstract: Titanium--in--Quartz geothermometry, originally pioneered by Wark and Watson [2006] then later modified by Kawasaki and Osanai [2008] and Thomas et al. [2010] promises accurate quartz crystallisation temperature determinations from straightforward measurements of Ti within the quartz lattice. These geothermometers are tested by applying them to a suite of contact metamorphosed quartzites from around the Ballachulish Igneous Complex in West Scotland. Results show that the original Ti--in--Quartz geothermometer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 64 publications
1
8
0
Order By: Relevance
“…Previous studies have shown that the Thomas et al . [] calibration underestimates the quartz recrystallization temperature in the case of contact metamorphism [ Morgan et al ., ] and overestimates Ti solubility in granite and rhyolite crystallizing from a melt by a factor of two to five [ Huang and Audétat , ]. However, Ashley et al .…”
Section: New Temperature Constraints: Methods and Resultsmentioning
confidence: 99%
“…Previous studies have shown that the Thomas et al . [] calibration underestimates the quartz recrystallization temperature in the case of contact metamorphism [ Morgan et al ., ] and overestimates Ti solubility in granite and rhyolite crystallizing from a melt by a factor of two to five [ Huang and Audétat , ]. However, Ashley et al .…”
Section: New Temperature Constraints: Methods and Resultsmentioning
confidence: 99%
“…Götze (2009) mentions that the concentration of defects and dislocations in (sub)grain boundaries in quartz results in a high CL intensity, while others associate differences in SEM-CL with differences in quartz impurity and/or point defect content in the quartz grain (e.g. Morgan et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The two different calibrations by Thomas et al (2010) and Huang & Aude¤ tat (2012) yield temperatures that can differ by more than 2008C at pressures of 0·2 GPa. Studies supporting both calibrations exist (Leeman et al, 2012;Wilson et al, 2012;Ashley et al, 2013;Aude¤ tat, 2013;Morgan et al, 2013;Kularatne & Aude¤ tat, 2014), suggesting that the two calibrations might be appropriate in different geological settings or that their success might be dependent on aTiO 2 (Leeman et al, 2012; Thomas & Watson, 2012;Wilson et al, 2012;Morgan et al, 2013;Kularatne & Aude¤ tat, 2014). It should be noted that an alternative TitaniQ calibration by Kawasaki & Osanai (2008), as well as the calibration by Wark & Watson (2006), does not include a pressure dependence and will not be included in the following discussion.…”
Section: T H E R M O M E T Ry Ti-in-quartz Thermometermentioning
confidence: 97%
“…Our samples do not contain rutile, so we can be sure that aTiO 2 51, but they do contain Fe^Ti oxides, which should fix aTiO 2 at some intermediate value during subsolidus quartz crystallization (Qtz2) (e.g. Ghiorso & Gualda, 2013), assuming that equilibrium can be achieved (see Huang & Audetat, 2012;Morgan et al, 2013). For melt-present crystallization, several studies demonstrate that in silicic volcanic systems, aTiO 2 typically varies by 50·5 between compositionally similar samples from the same location (Leeman et al, 2012;Aude¤ tat, 2013;Ghiorso & Gualda, 2013;Kularatne & Aude¤ tat, 2014).…”
Section: T H E R M O M E T Ry Ti-in-quartz Thermometermentioning
confidence: 99%